Large-Scale Hydromorphological Characteristics Of The Proglacial River Katun (Ob Headwaters) - Friedrich Seidl; Markus Reisenbüchler; Peter Rutschmann; Liubov V. Yanygina; Martin Schletterer (Geography, Environment, Sustainability)
During the industrialization in Europe, rivers were straightened and designed to fit human activities, thus nowadays only a few natural river systems remain as reference conditions as well as guiding principles for river restoration projects. Therefore, the natural state of some river types is often described using historic records and maps. This study aims to analyze the key characteristics of a pristine proglacial river Katun in the Altai mountains and contribute to the knowledge about reference conditions. For this purpose, hydromorphological characteristics like slope, sinuosity and river width of the river Katun were analysed and summarized using different GIS techniques. Additionally, pebble counts were carried out to assess the changing sediment composition along the longitudinal continuum. Combined with River Habitat Surveys and a one-dimensional flow simulation using HEC-RAS it was possible to give a holistic overview of the dynamic fluvial system Katun in its upper, middle and lower reaches. The results confirmed the relationship between the river and its surrounding topography as they clearly show the lateral development of the Katun. As shown for the individual parameters (e.g., slope, width, depth, flow velocity, shear stress), they influence each other and are strongly dependent and characteristic for each river section. In the context of revitalisation of straightened and / or channelized river courses, it is important to focus on the processes of this interaction and provide suitable space for lateral expansion. The study can be seen as a recommendation on how to analyse hydromorphological characteristics of fluvial systems as well as to establish guiding principles in river restoration using remote sensing.